2018
DOI: 10.1111/jcmm.13814
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 induces human mononuclear cell chemotaxis and adhesion and modulates monocyte‐to‐macrophage differentiation

Abstract: Type 2 diabetes mellitus (T2DM) is a cardiovascular risk factor which leads to atherosclerosis, an inflammatory disease characterized by the infiltration of mononuclear cells in the vessel. Bone morphogenetic protein (BMP)‐2 is a cytokine which has been recently shown to be elevated in atherosclerosis and T2DM and to contribute to vascular inflammation. However, the role of BMP‐2 in the regulation of mononuclear cell function remains to be established. Herein, we demonstrate that BMP‐2 induced human monocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
(112 reference statements)
0
34
0
Order By: Relevance
“…For instance, it has been shown that BMP-2 and PDGF-BB induce monocyte and macrophage chemotaxis (7,8,30,31). In addition, BMP-2 may modulate the polarization of macrophages toward an anti-inflammatory phenotype either positively or negatively (8,32). Nevertheless, one of the major side effects of BMP-2 in clinical use is rampant inflammation (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that BMP-2 and PDGF-BB induce monocyte and macrophage chemotaxis (7,8,30,31). In addition, BMP-2 may modulate the polarization of macrophages toward an anti-inflammatory phenotype either positively or negatively (8,32). Nevertheless, one of the major side effects of BMP-2 in clinical use is rampant inflammation (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2 expression has been described in a plethora of macrophage subtypes, with M1 macrophages secreting particularly high levels of BMP-2 (50,51). BMP-2 is also involved in monocyte chemotaxis and cell adhesion, and prevents their differentiation into M2 macrophages, demonstrating its role in pro-inflammatory signaling (52). M2 macrophages stimulate mesenchymal stem cell proliferation and osteogenic differentiation through BMP-2 signaling (53).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, we found that the decreased serum level of sST2 on the first day after MI and serum levels of hCRP and MMP-9 on the third day after MI correlate with high serum BMP-4 levels, which may indicate that BMP-4 exhibits anti-inflammatory activity. In addition, BMP-2 is known to induce chemotaxis of monocytes and disrupt their differentiation into anti-inflammatory M2 macrophages [ 27 ]. Perhaps, this can explain the absence of significant dynamics of serum levels of BMP-4 with anti-inflammatory activity in the early period of AMI in our study.…”
Section: Discussionmentioning
confidence: 99%